Teknologi Pendidikan: Pemanfaatan Teknologi dalam Pendidikan Pasca Pandemi - Unik Hanifah Salsabila; Asri Putri Satya Insani; Habib Mustofa; Muhammad Excel Zarin Kalma; Muhammad Iqbal Wibisono (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2023)
The presence of the pandemic in the first quarter of 2020 also changed the order of human life. All activities that were originally carried out in person changed to online meetings using technological tools and digital platforms. This is no exception for the education sector. In the world of education, learning, which was originally carried out face-to-face, was replaced by online meetings. This lasted for at least a period of 2 years. With the change of learning space, it also changes habits so that it affects the quality of education. In this journal, we try to examine various kinds of changes that exist in the post-pandemic education world as well as the benefits and functions of educational technology from the pandemic era to post-pandemic. In this observation we use qualitative methods. Interviews are the data collection technique we choose. The technical spread is through a google form questionnaire, the results obtained from this study, namely the use of post-pandemic technology greatly affect the learning process. Post-pandemic learning provides benefits in the form of time and place efficiency. However, post-pandemic learning has not fully run well, because educators and students are less focused on learning sessions and interfere with students' understanding of the material presen.